ORIGINAL PEOPLES IN BRAZIL AND IN MEXICO: REFLECTIONS ON CURRICULUM AND INTERCULTURALITY - Nascimento, Sueli do [UNESP]; Carvalho, Alonso Bezerra de [UNESP]; Aguirre, Cynthia Coronado (Unesp-faculdade Ciencias & Letras, 2022)
This article aims to work with dialogues between researchers to encourage reflections on teacher training in Brazil and Mexico, with a view to a meaningful educational practice through an intercultural training in which education and spirituality are connected. Search the literature for themes related to the subject; discuss the review of the curriculum that supports teacher education, pointing out contents that in the classroom stimulate debate both on curriculum and on interculturality. For that, prevails the opinion that the most indicated are the subjects qualified in a self-reflective educational practice, Freire pattern. The intercultural teaching and learning process must be supported by Latin American thinkers and writers, including the knowledge of native peoples. The proposal is to rethink the curricula of both countries, with discussions that encourage researchers to reflect on the deconstruction of Eurocentric ideas and the historical linearity that permeates the curricula used in teacher education.
Keywords: Education; Curriculum; Training; Interculturality; Teachers.